What agenda of and for women? Gender, politics, and institutional transformation in Rome - Farina, Fatima (Frontiers in Political Science, 2025)
IntroductionWomen’s political representation in Italy has increased in recent decades, yet significant gender gaps persist across elected and appointed offices. The Municipality of Rome represents a distinctive case, as it is the only Italian city subdivided into directly elected Municipi. Differently, other large cities such as Milan, Turin, Bologna, and Naples are organised into zones, districts, or municipalità without elected bodies, limiting local political autonomy. This institutional uniqueness makes Rome an important site for investigating how gender, profession, and political alignment shape women’s political visibility and participation.MethodsThe study employs a mixed-method approach. It combines quantitative data (2016–2021) on elected and appointed offices, disaggregated by sex, with qualitative analysis of the professional backgrounds and political alignments of elected representatives in Rome. Furthermore, the agendas of Equal Opportunities Commissions across the Municipi are examined to assess how gender equality is operationalised at the local level.ResultsThe findings reveal persistent inequalities. Women are more concentrated in education, social services, and intellectual professions, whereas men dominate entrepreneurial, managerial, and technical roles. Political alignment also influences gender balance: the left and the Five Star Movement (M5S) exhibit higher female participation, particularly from academic and social sectors, while the centre and right remain strongly tied to business and legal professions. Despite quota laws and equality regulations, women continue to be underrepresented in appointed roles and mayoral offices. The Equal Opportunities Commissions display heterogeneous agendas, combining advances in gender mainstreaming with the persistence of structural barriers.DiscussionThe Roman case illustrates the ambivalence of gender equality policies. While decentralised institutions and local commissions provide meaningful spaces for women’s participation, entrenched power structures still hinder substantive transformation. Compared with other Italian cities, Rome’s political decentralisation amplifies these dynamics, offering broader insights into both the limits and the potential of equality measures in local politics.